The therapeutic potential of targeting exchange protein directly activated by cyclic adenosine 3′,5′-monophosphate (Epac) for central nervous system trauma - Alba Guijarro-Belmar; Dominik Mateusz Domanski; Xuenong Bo; Derryck Shewan; Wenlong Huang (Neural Regeneration Research, 2021)
Millions of people worldwide are affected by traumatic spinal cord injury, which usually results in permanent sensorimotor disability. Damage to the spinal cord leads to a series of detrimental events including ischaemia, haemorrhage and neuroinflammation, which over time result in further neural tissue loss. Eventually, at chronic stages of traumatic spinal cord injury, the formation of a glial scar, cystic cavitation and the presence of numerous inhibitory molecules act as physical and chemical barriers to axonal regrowth. This is further hindered by a lack of intrinsic regrowth ability of adult neurons in the central nervous system. The intracellular signalling molecule, cyclic adenosine 3′,5′-monophosphate (cAMP), is known to play many important roles in the central nervous system, and elevating its levels as shown to improve axonal regeneration outcomes following traumatic spinal cord injury in animal models. However, therapies directly targeting cAMP have not found their way into the clinic, as cAMP is ubiquitously present in all cell types and its manipulation may have additional deleterious effects. A downstream effector of cAMP, exchange protein directly activated by cAMP 2 (Epac2), is mainly expressed in the adult central nervous system, and its activation has been shown to mediate the positive effects of cAMP on axonal guidance and regeneration. Recently, using ex vivo modelling of traumatic spinal cord injury, Epac2 activation was found to profoundly modulate the post-lesion environment, such as decreasing the activation of astrocytes and microglia. Pilot data with Epac2 activation also suggested functional improvement assessed by in vivo models of traumatic spinal cord injury. Therefore, targeting Epac2 in traumatic spinal cord injury could represent a novel strategy in traumatic spinal cord injury repair, and future work is needed to fully establish its therapeutic potential.